Evaluation of Business Intelligence Projects Success - Teixeira, Ana (2019)
Teixeira, A., Oliveira, T., & Varajão, J. (2019). Evaluation of Business Intelligence Projects Success: a case study. Business Systems Research, 10(1), 1-12. https://doi.org/10.2478/bsrj-2019-0001